Release phenomena and toxicity in polymer-based dental restorative materials - Fano, V.; Shatel, M.; Tanzi, M.L. (Acta Biomedica Atenei Parmensis, 2007)
In this work, the origin of the release phenomena occuring in resin-based dental restorative materials is demonstrated using confocal fluorescence microscopy and tapping mode atomic force microscopy techniques. The surface structure (microcavities, protruded filler particles, grain boundaries, and cracks) produced by water environment on the surface of composite resins and resin-modified glass-ionomeric cements (RMGICs) are shown. The water absorption and the subsequent weight decrease, induced by leaching process, have been measured by gravimetric analysis. The different toxicity effects induced by the component release are described.